Oncogene- and Oxidative Stress-Induced Cellular Senescence Shows Distinct Expression Patterns of Proinflammatory Cytokines in Vascular Endothelial Cells - Etsu Suzuki; Masao Takahashi; Shigeyoshi Oba; Hiroaki Nishimatsu (The Scientific World Journal)
Senescent cells are metabolically active and produce a variety of proinflammatory cytokines. It was previously reported that atherosclerotic plaques contain senescent cells, suggesting that senescence may contribute to the progression of atherosclerosis. In this study, we induced cellular senescence in vascular endothelial cells (VECs) using hydrogen peroxide (H2O2) or an adenovirus that expresses a constitutively active mutant of Ras (AdRas12V) and studied the expression of cytokines. Both H2O2 treatment and AdRas12V infection induced senescence in VECs, as assessed by senescence-associated -Gal activity and the expression of proteins such as . In addition, both treatments induced the expression of a variety of cytokines, including interleukin-1 (IL-1) and nerve growth factor (NGF). AdRas12V infection induced IL-1 expression more significantly than H2O2 treatment, whereas both treatments induced comparable mRNA and protein expression levels of NGF. These results suggest that senescent cells express different patterns of proinflammatory cytokines, depending on the trigger that induced senescence. It is therefore possible that senescent cells can differentially induce inflammation in the surrounding tissues, depending on the cause of senescence.